2012
DOI: 10.1177/0363546511435084
|View full text |Cite
|
Sign up to set email alerts
|

Sports Activity After Osteochondral Transplantation of the Talus

Abstract: Patients engage in fewer, less frequent sporting activities when a symptomatic osteochondral lesion (OCL) at the talus is present. Talar osteochondral transplantation shows good clinical midterm results and allows patients to return to sporting activity. However, we found patients modify their postoperative sporting activities, and we noted a reduction of participation in high-impact and contact sports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 27 publications
4
51
0
4
Order By: Relevance
“…Alle Patienten wurden präoperativ klinisch mit dem American Orthopaedic Foot and Ankle Society (AOFAS) Score [19] und der visuellen Analogskala für Schmerz (VAS) [20] untersucht. Alle Patienten waren für eine autologe osteochondrale Transplantation am Talus geplant und wurden mit dem "Osteochondral Autograft Transfer System" (OATS, Arthrex, Naples, FL, USA) operativ versorgt, wie in der Literatur zuvor beschrieben [21,22]. Ausschlusskriterien für die Studienteilnahme waren noch nicht geschlossene Wachstumsfugen, vorherige Traumata oder Distorsionen des OSG, Bandinstabilitäten des OSG und Revisionsoperationen am OSG.…”
Section: Materials Und Methodeunclassified
“…Alle Patienten wurden präoperativ klinisch mit dem American Orthopaedic Foot and Ankle Society (AOFAS) Score [19] und der visuellen Analogskala für Schmerz (VAS) [20] untersucht. Alle Patienten waren für eine autologe osteochondrale Transplantation am Talus geplant und wurden mit dem "Osteochondral Autograft Transfer System" (OATS, Arthrex, Naples, FL, USA) operativ versorgt, wie in der Literatur zuvor beschrieben [21,22]. Ausschlusskriterien für die Studienteilnahme waren noch nicht geschlossene Wachstumsfugen, vorherige Traumata oder Distorsionen des OSG, Bandinstabilitäten des OSG und Revisionsoperationen am OSG.…”
Section: Materials Und Methodeunclassified
“…Other studies showed that 63-85% of athletes who underwent AOT were able to return to preinjury levels of sports activity [59,61]. However, in a study by Paul et al [61], patients engaged in high-impact and contact sports required a partial modification of the sporting activities and a reduction of participation. With regards to long-term followup, to our knowledge, no study has been established.…”
Section: Replacement Procedures Autologous Osteochondral Transplantationmentioning
confidence: 96%
“…Reparative surgical techniques such as bone marrow stimulation for lesions of less than 15 mm in diameter yield good functional outcomes in short term follow-up [56,63] . Larger lesions are best treated with replacement strategies including autologous osteochondral transplantion (AOT) ( Figure 7) or other techniques including autologous chondrocyte implantation [64][65][66] . Both reparative and replacement strategies have been evaluated in regards to return to soccer however the evidence is limited in both groups.…”
Section: Ocl'smentioning
confidence: 99%
“…The mean time to return to sport was 15 wk after marrow stimulation and 19 wk after bone grafting (not AOT's). More recently, Paul et al [64] assessed sports activity after talar AOT's in 131 patients with a mean age of 31 years. Seventy percent were either very satisfied or satisfied by the procedure and 85% required no analgesia when currently involved in sports.…”
Section: Ocl'smentioning
confidence: 99%